TECHNICAL FEASIBILITY IN THE APPLICATION OF INDUSTRIAL SLAG FOR USE IN ENGINEERING WORKS - Evia Escalante, Mario Alejandro
This paper will show the experimental results obtained by generating a dosage between the soil to be studied and the industrial slag and thus provide optimal amounts of this material (industrial slag) in the improvement of its load capacity to give a possible use in engineering, which serves as an alternative for soil improvement and basis for further studies conducted through SENA research workshops